Analysis Of The Influence Of Price, Promotion And Service Quality On Customer Satisfaction In Online Grab Ojek Services, Kediri City - Marlina, Nana; Winarko, Sigit Puji; Linawati, Linawati (Universitas Nusantara PGRI Kediri, 2023)
Research Objective:This study has the objective of how the influence of price, promotion, and service quality on Grab customer satisfaction in Kediri City. Research Method: In taking this sample using the technique of purposive sampling by using a causal quantitative approach and calculations based on the Slovin formula so that a sample of 100 respondents was taken. This study makes use of Google Forms which has been tested for its validity and reliability to distribute questionnaires for data collection. Data analysis technique usedSPSS version 23 in research for the hypothesis and the coefficient of determination. Research Finding: The results obtained prove that price, promotion and service quality all have a significant positive influence on customer satisfactionGrab in the Kediri City area. It is hoped that this research, will make customers feel satisfied in using it and the company can also improve its competitiveness.